Rethinking the regions: Indigenous peoples and regional development. Issue 11 (2nd November 2019) - ,; Lee, Emma; Eversole, Robyn
ABSTRACT: This paper contributes to a more in-depth theorization of the role of community and culture in regional development with a specific reference to the diverse communities who identify as Indigenous peoples. The concept of Indigenous regional development is used to describe how Indigenous cultural perspectives on regions, knowledge and the kinds of relationships that can generate innovation are distinctive from mainstream scholarly and policy conceptualizations. Indigenous regional development opens up new conceptual terrain for both regional development theory and policy, creating new opportunities for cross-cultural collaboration and regional innovation.